The State of Tax Policy in the Central Asian and Transcaucasian Newly Independent States (NIS) - Escolano, Julio; Shome, Parthasarathi (Washington, D.C. : International Monetary Fund, 1993)
Two possible tax policy strategies for the NIS are: (1) an optimal nondistortionary tax structure as a one-shot action; and (2) a structure with identifiable and clearly understood distortionary elements as a temporary phenomenon to close the fiscal gap. An assessment of NIS tax structures reveals that they conform to neither. They are rapidly acquiring complex features comprising multiple rates, exemptions, and other difficult-to administer properties, with uncertain ramifications for efficiency, equity, and the fiscal deficit. Steady--and perhaps prolonged--effort needs to be made if simple, broad-based, and revenue-productive tax structures are to be achieved. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet